Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
e = 4
Step-by-step explanation:
3 ( e - 3 ) - 7 ( 2e - 8 ) - ( e - 1 ) = 0
The first step to solving such an equation is to distribute. Multiply the term outside of the parentheis by every term inside of the parenthesis,
3e - 9 - 14e + 56 - e + 1 = 0
Simplify, combine like terms,
3e - 9 - 14e + 56 - e + 1 = 0
3e - 14e - e - 9 + 56 + 1 = 0
-12e + 48 = 0
Inverse operations,
-12e + 48 = 0
+12e +12e
48 = 12e
/12 /12
4 = e
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.